2017
DOI: 10.1093/nar/gkx100
|View full text |Cite
|
Sign up to set email alerts
|

Alternative DNA structure formation in the mutagenic human c-MYC promoter

Abstract: Mutation ‘hotspot’ regions in the genome are susceptible to genetic instability, implicating them in diseases. These hotspots are not random and often co-localize with DNA sequences potentially capable of adopting alternative DNA structures (non-B DNA, e.g. H-DNA and G4-DNA), which have been identified as endogenous sources of genomic instability. There are regions that contain overlapping sequences that may form more than one non-B DNA structure. The extent to which one structure impacts the formation/stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 84 publications
(90 reference statements)
2
31
0
Order By: Relevance
“…The complete analysis of the hyperdiploid stemline showed that it contained recurrent structural rearrangements involving chromosomes 1, 2, 3, 4, 5, 6, 8, 10, 11, 12, 15, 16, 17, 18, and 19. Numerical gains of chromosomes X, 1,2,3,4,7,11,14,16,17,18,19,20, and 21 were present. Of note, the only chromosome homologues that did not have structural rearrangements were chromosomes 7, 9, 13, 14, 20, 21, 22, (19)t (5;19;5),+20,+20,+21,+21 [5].…”
Section: Resultsmentioning
confidence: 98%
“…The complete analysis of the hyperdiploid stemline showed that it contained recurrent structural rearrangements involving chromosomes 1, 2, 3, 4, 5, 6, 8, 10, 11, 12, 15, 16, 17, 18, and 19. Numerical gains of chromosomes X, 1,2,3,4,7,11,14,16,17,18,19,20, and 21 were present. Of note, the only chromosome homologues that did not have structural rearrangements were chromosomes 7, 9, 13, 14, 20, 21, 22, (19)t (5;19;5),+20,+20,+21,+21 [5].…”
Section: Resultsmentioning
confidence: 98%
“…Notably, the 23-bp TFR in the c-MYC gene near a translocation breakage hotspot in lymphoma, as discussed above, was found in three translocation events in the human cancer translocation dataset (data not shown). Although this G-rich repeat also has the potential to form a G-quadruplex structure, we recently demonstrated that this particular sequence preferentially forms a stable H-DNA structure ( Del Mundo et al, 2017 ). Moreover, we previously found that a variant of this sequence that forms H-DNA only, but not the sequence that supports G-quadruplex formation only, stalls transcription similar to the native sequence ( Belotserkovskii et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…These alternative structures include triple-helices, hairpins, cruciforms, and slipped structures, and they are more likely to form at particular repetitive sequences such as mirror repeats, inverted repeats, direct repeats, and short tandem repeats (Wells 2007). Noncanonical secondary structures are associated with increased mutability according to in vitro studies of prokaryotic (Todd and Glickman 1982;Hoede et al 2006) and eukaryotic cells (Wang and Vasquez 2004;Wang et al 2006Wang et al , 2008Voineagu et al 2008;Lipps and Rhodes 2009;Biffi et al 2013;Lu et al 2015;Bacolla et al 2016;Kaushik Tiwari et al 2016;Del Mundo et al 2017;Kouzine et al 2017).…”
mentioning
confidence: 99%